استخدام تطبيق "أليف بي" في ترقية المهارات اللغوية لدى الطلاب المبتدئين - Lukman Al Hakim; Achmad Idris Kamalullah; Tuti Qurrotul Aini; Achmad Tabrani; Ali Mahmoud Al-Asmai Ismail (Arabiyyatī: Journal of Arabic Language Education, 2024)
Abstract This study examines the linguistic skills essential for learning Arabic, emphasizing its status as one of the world's most spoken languages, with approximately 274 million speakers. The research focuses on the four fundamental language skills: listening, reading, writing, and speaking, asserting that mastery of these skills is crucial for effective use of the Arabic language. Definitions of language by prominent linguists like Ibn Jinni and Ibn Khaldun are discussed, highlighting that language is a system of sounds and structures conveying specific meanings, which underscores the importance of these linguistic skills. The study introduces the "AlifBee" application developed by AlifBee Limited under the Nama Foundation, highlighting its role in facilitating Arabic language learning for non-native speakers through interactive lessons powered by artificial intelligence and modern technology. The app's use of culturally relevant educational materials helps improve beginners' Arabic skills. The challenges faced by beginners in learning Arabic, such as reading and writing difficulties and mastering vocabulary, are also discussed. The study emphasizes the need for engaging educational tools and applications that support the learning objectives. Additionally, it underlines the importance of a communicative approach in teaching Arabic, integrating linguistic theories with the language's primary function as a tool for communication. Furthermore, the research explores the Common European Framework of Reference for Languages (CEFR) and its application in Arabic language teaching, stressing the importance of horizontal and vertical synchronization in acquiring language skills to ensure balanced learning. Finally, the study provides recommendations for improving Arabic language education for beginners, such as creating supportive learning environments, using diverse teaching methods, and continuously assessing progress to provide constructive feedback.